Parametric tracking across multiple cameras - Sebastian, P. (Universiti Putra Malaysia Press, 2017)
This paper presents a tracking method based on parameters between colour blobs. The colour blobs are obtained from segmenting the overall target into multiple colour regions. The colour regions are segmented using EM method that determines the normal colour distributions from the overall colour pixel distribution. After segmenting into different regions on the different colour layers, parameters can be generated between colour regions of interest. In this instance, the colour regions of interest are the top and bottom colour regions. The parameters that are generated from these colour regions are the vector magnitude, vector angle and the value difference between colour regions. These parameters are used as a means for tracking targets of interest. These parameters are used for tracking the target of interest across an array of cameras which in this instance are three cameras. Three cameras have been set up with different background and foreground conditions. The summarised results of tracking targets across three cameras have shown that the consistency of colour regions across different cameras and different background settings provided sufficient parameters for targets to be tracked consistently. Example of tracking performance across three cameras were 0.88, 0.67 and 0.55. The remaining tracking performances across three cameras are shown in Table 2. The tracking performance indicate that the parameters between colour regions were able to be used for tracking a target across different cameras with different background scenarios. Based on results obtained, parameters between segmented colour regions have indicated robustness in tracking target of interest across three cameras. © 2017 Universiti Putra Malaysia Press.